Problems of poetic translation - M. R. Arpentieva (Омский научный вестник: Серия "Общество. История. Современность")
This work is devoted to the problems of translation as a process and result of understanding, dialogue with the text and its author in the translation process. Translation is an understanding activity requiring trans-ordinate knowledge of both own and translated language. Difficulties in translation are well illustrated by translations of poems. The teaching of a foreign language in the context of the translation of poetic works is one of the most productive technologies for developing an understanding of language as an integral, sociocultural phenomenon. Poetry accounts for a tiny proportion of world translation output. Case studies and examples taken from poetry, however, have dominated theory-building in translation studies at the expense of more frequently translated genres. Poetry translation may be defined as relaying poetry into another language. Apart from transforming text, poetry translation also involves cognition, discourse, and action by and between human and textual actors in a physical and social setting. Poetry translation is typically overt. Poetry translators are concerned to interpret a source poem’s layers of meaning, to relay this interpretation reliably, and/or to ‘create a poem in the target language which is readable and enjoyable as an independent, literary text. Poetry translation involves challenges and these are highlighted in this article